2015
DOI: 10.1002/brb3.413
|View full text |Cite
|
Sign up to set email alerts
|

Neural basis of hierarchical visual form processing of Japanese Kanji characters

Abstract: IntroductionWe investigated the neural processing of reading Japanese Kanji characters, which involves unique hierarchical visual processing, including the recognition of visual components specific to Kanji, such as “radicals.”MethodsWe performed functional MRI to measure brain activity in response to hierarchical visual stimuli containing (1) real Kanji characters (complete structure with semantic information), (2) pseudo Kanji characters (subcomponents without complete character structure), (3) artificial ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 54 publications
(91 reference statements)
0
2
0
Order By: Relevance
“…The acquisition of literacy skills varies according to writing systems (Koyama, Hansen, & Stein, 2008). While alphabetic or syllabic scripts such as the English alphabet employ phonographic systems in which a symbol is mapped onto a sound unit (Shaywitz, Shaywitz, Fletcher, & Escobar, 2015), the Japanese writing system uses not only phonographic but also logographic systems in which a symbol is mapped onto either a word or a meaningful unit, such as in Chinese (Higuchi et al, 2015;Koyama et al, 2008;Uno Wydell, Haruhara, Kaneko, & Shinya et al, 2009). In addition, logographic Japanese characters have visual forms that are different from alphabetic letters.…”
Section: Introductionmentioning
confidence: 99%
“…The acquisition of literacy skills varies according to writing systems (Koyama, Hansen, & Stein, 2008). While alphabetic or syllabic scripts such as the English alphabet employ phonographic systems in which a symbol is mapped onto a sound unit (Shaywitz, Shaywitz, Fletcher, & Escobar, 2015), the Japanese writing system uses not only phonographic but also logographic systems in which a symbol is mapped onto either a word or a meaningful unit, such as in Chinese (Higuchi et al, 2015;Koyama et al, 2008;Uno Wydell, Haruhara, Kaneko, & Shinya et al, 2009). In addition, logographic Japanese characters have visual forms that are different from alphabetic letters.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, Tamaoka and Kiyama (2013) showed that visually complex kanji with low frequency elicited a heavier cognitive load within single kanji processing. Because visual complexity is an important factor when recognizing kanji (see also : Higuchi, Moriguchi, Murakami, Katsunuma, Mishima, & Uno, 2016), stroke counts must be controlled for conditions within experiments involving kanji.…”
Section: Strokes (Visual Complexity)mentioning
confidence: 99%